New records of spirurid nematodes (Nematoda, Spirurida, Guyanemidae, Philometridae & Cystidicolidae) from marine fishes off New Caledonia, with redescriptions of two species and erection of Ichthyofilaroides n. gen - Moravec, František; Justine, Jean-Lou (Parasite (Paris, France), 2020)
Recent examinations of spirurid nematodes (Spirurida) from deep-sea or coral reef marine fishes off New Caledonia, collected in the years 2006-2009, revealed the presence of the following five species: Ichthyofilaroides novaecaledoniensis (Moravec et Justine, 2009) n. gen., n. comb. (transferred from Ichthyofilaria Yamaguti, 1935) (females) (Guyanemidae) from the deep-sea fish Hoplichthys citrinus (Hoplichthyidae, Scorpaeniformes), Philometra sp. (male fourth-stage larva and mature female) (Philometridae) from Epinephelus maculatus (Serranidae, Perciformes), Ascarophis (Dentiascarophis) adioryx Machida, 1981 (female) (Cystidicolidae) from Sargocentron spiniferum (Holocentridae, Beryciformes), Ascarophis (Ascarophis) nasonis Machida, 1981 (males and females) from Naso lituratus and N. unicornis (Acanthuridae, Perciformes), and Ascarophisnema tridentatum Moravec et Justine, 2010 (female) from Gymnocranius grandoculis (Lethrinidae, Perciformes). Two species, I. novaecaledoniensis and A. nasonis, are redescribed based on light microscopical (LM) and scanning electron microscopical (SEM) examinations, the latter used in these species for the first time. Morphological data on the specimen of A. tridentatum from the new host species are provided. Philometra sp. (from E. maculatus) most probably represents a new gonad-infecting species of this genus. The newly established genus Ichthyofilaroides n. gen. is characterized mainly by the presence of a small buccal capsule and by the number and distribution of cephalic papillae in the female; it is the sixth genus in the Guyanemidae.
Keywords: Dracunculoidea; druhová specificita; Male; Fish Diseases; Coral Reefs; Holocentridae; New Caledonia; mužské pohlaví; Oceans and Seas; Serranidae; Species Specificity; ryby; Nová Kaledonie; Spirurida Infections; Fishes; hostitelská specificita; Host Specificity; larva; Animals; ženské pohlaví; Microscopy, Electron, Scanning; Acanthuridae; zvířata; nemoci ryb; Spirurida; South Pacific; Larva; infekce hlísticemi řádu Spirurida; Female; oceány a moře; mikroskopie elektronová rastrovací; Hoplichthyidae; korálové útesy